Women Worker Pay Gaps: 'Sticky Floors' And 'Glass Ceilings', in Indonesia - Wahyuni, Sri; Ranita, Sylvia Vianty; Maidalena, Maidalena; Bachtiar, Nasri; Hasni, Khairul (Jurnal Economia, 2025)
The study tested wage disparities across Indonesian wage distribution the peak of women's careers. Using data from the fifth wave of the Indonesian Family Life Survey (IFLS-5), the study employed logistic regression analysis. The results show that the influence of work types and health insurance on women's wage disparities has a significant and negative impact on the Glass Ceiling (GC) phenomenon, especially on private female workers, farm women workers, and unpaid female labourers. The main results of this study show that the type of work that female workers do in Indonesia is still classified the Sticky Floor (SF). The study emphasizes the need for interventions to address gender inequality in the Indonesian workforce, including gender-inclusive policies, audits, equal pay, mentorship programs, workshops, and training sessions, to create a more equitable workforce.